EMPOWERING THE LOCAL RESOURCES BASED ON THE SOCIETY NEEDS (Case Study on Bottom up Social Change in Gajahrejo Village, Gedangan Districts, Malang Regency) - S. Mundzir; Z Zulkarnain (Faculty of Education Universitas Negeri Malang, 2018)
This study was aimed at describing several issues related to the people living in Gajahrejo Village, Gedangan Districts, Malang Regency including: a) the condition of social economy, b) the potential of natural resources, c) the profile of the society needs, d) the profile of the community development by making the most of the local potential, and e) the pattern of community development especially in dusun Bajulmati. The research design of this study was case study which took place in Gajahrejo Village and focused on Dusun Bajulmati. The data was collected by using in-depth interview which was accompanied by focus group discussion (FGD), observation technique, and documentation involving research participants who were several respected figures living in Dusun Bajulmati. The result of the study was in the form of information related to the abundant natural resources which were used to develop the society. However, the human resources were not sufficient enough because the education was relatively low. The existing positive points were that the people living in Dusun Bajulmati were hard workers and that they were supported by agent of change especially Mr. Shohibul Izar who was highly dedicated to develop the community in Dusun Bajulmati. Based on the result of the study, it was suggested that there should be a traininginstitution which was willing to give life skill education and practice in order to improve the quality of the society. In addition, an organization that could help the farmers who worked in forest so there would be a good relation between the State Forestry Company and the people living Gajahrejo village as farmers who worked in forest by planting intercultural crops which was the main income for most of people living near the forest. Keywords: empowering, local potential, and community development